Taste alteration and its relationship with nutritional status among cancer patients receiving chemotherapy, cross-sectional study - Al-Amouri, Fatima Masoud; Badrasawi, Manal (PLOS ONE, 2024)
The aim of this study is to determine the prevalence of taste alterations (TAs) during chemotherapy and their association with nutritional status and malnutrition. In addition to the associated factors with TA, including sociodemographic health-related factors and clinical status, and to investigate coping strategies to manage TA. A multicenter cross-sectional design study was conducted on 120 cancer patients aged at least 18 who had been undergoing at least one round of chemotherapy. TAs were evaluated using the chemotherapy-induced taste alteration scale (CiTAS), the malnutrition universal screening tool (MUST) was used for nutritional screening, the antineoplastic side effects scale (ASES) was used for subjective assessment of chemotherapy side effects, and the Charlson comorbidity index (CCI) was used for comorbidity assessment. SPSS21 software was used to analyze the data, and the independent T-test and one-way ANOVA test were used to determine the association between TAs and a variety of related variables. The prevalence of TAs was 98.3%. Among participants, 48.3% were at low risk of malnutrition, 20% at medium risk, and 31.7% at high risk. Malnutrition risk was associated with taste disorders (p<0.05). Patients’ age, gender, educational level, and physical status were associated with TAs (p<0.05). Type of cancer, chemotherapy regimen, and number of chemotherapy cycles were also associated with TAs (p<0.05). A variety of antineoplastic side effects were associated with TAs (p<0.05), including nausea, vomiting, dry mouth, sore mouth and throat, excessive thirst, swallowing difficulty, appetite changes, weight loss, dizziness, lack of energy, disturbed sleep, anxiety, and difficulty concentrating. TAs were associated with an increased number of comorbidities, and individuals with diabetes, pulmonary diseases, and hypertension were associated with TAs (P<0.05). Patients in this study rarely practice self-management strategies to cope with TAs. A high prevalence (98.3%) of TAs in cancer patients receiving chemotherapy was found, and it was linked to a variety of negative outcomes. Chemotherapy-induced TAs are an underestimated side effect that requires more attention from patients and health care providers.